Analisis Implementasi Sistem Payroll Berbasis Digital dalam Meningkatkan Efisiensi dan Kesejahteraan Karyawan - Arifin, Zainul; Wirahadiyono, I Made Adiyasa; Sugiharto, Didik Priyo (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
In the ever-evolving digital era, information technology (IT) plays a vital role in enhancing efficiency and productivity in the business sector. The larger a company becomes, the more it relies on IT, due to the increasing amount of data that needs to be managed. This research focuses on Red Coffee Pandaan, a company engaged in the food and beverage industry with affordable offerings. The aim of this study is to analyze the implementation process of a digital payroll system within the company. In addition, the research measures the impact of the digital payroll system on payroll efficiency. A qualitative research method was used, involving observation, interviews, and documentation for data collection. The results show that implementing a digital payroll system can improve the efficiency of payroll processing by reducing human error and speeding up processing time. Moreover, the system enhances employee welfare by ensuring clear and accurate salary payments. It is expected that this research will assist businesses in adopting technology that supports more efficient human resource management.